Application of Quality Function Deployment (QFD) in Industrial Management: A Case Study Approach to Product Development Optimization - Kalembo, Zuberi; Nyandoro, Amara; Okoroma, Chike; Phahlane, Lerato; Mekonnena, Tewodros (Publika Bersama Nusantara, 2025)
This study investigates the application of Quality Function Deployment (QFD) as a systematic approach to improve product development processes in industrial management. The research demonstrates how QFD methodology translates customer requirements into technical specifications, enabling organizations to prioritize resources effectively and enhance customer satisfaction. Through a case study implementation in a manufacturing environment, this paper examines the House of Quality matrix development, competitive analysis, and technical correlation assessment. Results indicate that QFD implementation leads to improved product quality, reduced development time, and enhanced alignment between customer expectations and technical capabilities. The findings contribute to the understanding of QFD's role in strategic industrial management and provide practical insights for manufacturing organizations seeking to optimize their product development processes.